Combined pretreatment with torrefaction and washing using torrefaction liquid products to yield upgraded biomass and pyrolysis products. (March 2017) - Chen, Dengyu; Mei, Jiaming; Li, Haiping; Li, Yiming; Lu, Mengting; Ma, Tingting; Ma, Zhongqing
Highlights: Torrefaction liquid washing pretreatment greatly reduced the metals of cotton stalk. Torrefaction improved the fuel property while it increased metals contents of sample. Torrefaction liquid washing reduced the secondary cracking of pyrolysis volatiles. Torrefaction greatly reduced the acids while it increased the phenols in bio-oil. Combined washing and torrefaction pretreatment preserved advantages of each method. Abstract: This study presented an approach to upgrade biomass and pyrolysis products using a process based on torrefaction liquid washing combined with torrefaction pretreatment. The torrefaction of cotton stalk was first conducted at 250 °C for 30 min and then the resulting torrefaction liquid products were collected and reused to wash cotton stalk. The pyrolysis of the original and pretreated cotton stalk was performed at 500 °C for 15 min in a fixed-bed reactor. The results indicated that the combined pretreatment obviously reduced the metallic species in cotton stalk, decreased the water and acids contents while promoted phenols in bio-oil, declined the ash content in biochar, as well as improved the heating value of non-condensable gas. Overall, the combined pretreatment did not only allow to reuse the liquid products issued from torrefaction pretreatment but also improved the quality of biomass and the pyrolysis products, making it a novel promising pretreatment method.